2018
DOI: 10.1186/s12974-018-1317-z
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of systemic oxidative stress and mesial temporal network degeneration in Parkinson’s disease with and without cognitive impairment

Abstract: BackgroundTo identify the vulnerable areas associated with systemic oxidative stress and further disruption of these vulnerable areas by measuring the associated morphology and functional network alterations in Parkinson’s disease (PD) patients with and without cognitive impairment.MethodsThis prospective study was approved by the institutional review board of KCGMH, and written informed consent was obtained. Between December 2010 and May 2015, 41 PD patients with different levels of cognitive functions and 29… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 40 publications
2
20
0
1
Order By: Relevance
“…Partial correlations among disease severity, specific brain atrophy, and vascular markers The PD signature of regional atrophy in this study was characterized by the predominant involvement of the left parahippocampus, bilateral posterior cingulate gyrus, fusiform, left temporal gyrus, and cerebellum, in addition to being correlated with disease severity, findings which were also supported by our previous studies [64,65]. After controlling for age and sex, volume changes in the left parahippocampus were weakly to moderately correlate with VCAM-1 expression levels.…”
Section: Vcam-1 and Mirna Profiles As Vascular Inflammation Indicatorsupporting
confidence: 90%
See 1 more Smart Citation
“…Partial correlations among disease severity, specific brain atrophy, and vascular markers The PD signature of regional atrophy in this study was characterized by the predominant involvement of the left parahippocampus, bilateral posterior cingulate gyrus, fusiform, left temporal gyrus, and cerebellum, in addition to being correlated with disease severity, findings which were also supported by our previous studies [64,65]. After controlling for age and sex, volume changes in the left parahippocampus were weakly to moderately correlate with VCAM-1 expression levels.…”
Section: Vcam-1 and Mirna Profiles As Vascular Inflammation Indicatorsupporting
confidence: 90%
“…The parahippocampus is a key component of the human ventral temporal cortex, which has the function of visual categorization and recognition [66], is part of the salience network that functions in memory retrieval [67], and is part of the default-mode network involved in memory encoding [68]. Our previous study demonstrated that mesial temporal network degeneration interacts with systemic oxidative stress and cognitive impairment in PD patients [65]. In parahippocampal gyrus brain tissue, the accumulation of alpha-synclein is directly related to the level of beta-amyloid and the Braak tangle stage and can predict cognitive status in PD dementia patients [69].…”
Section: Vcam-1 and Mirna Profiles As Vascular Inflammation Indicatormentioning
confidence: 99%
“…Our previous study indeed demonstrated the elevation of plasma nuclear DNA in PD which can even occur in early-onset PD patients [15]. In addition, higher peripheral apoptotic lymphocytes may be associated with a decreased cognition-associated functional network in PD patients with cognitive deficit [5].…”
Section: Possible Pathophysiology Of Altered Glymphatic System and Oxmentioning
confidence: 62%
“…In PD patients, neuroinflammation interacting with systemic oxidative stress may induce further CNS reactive astrogliosis [5], potentially impairing the glymphatic system. In addition, aging, a primary risk factor of PD, has been found to associate with decreased glymphatic activity and could be attributed to increased reactive gliosis.…”
Section: Introductionmentioning
confidence: 99%
“…It has been recognized that the autonomic nervous system plays a pivotal role in the regulation of lung ventilation, gas exchange, and airway smooth muscle function [8]. The observation that levodopa has a limited impact on the improvement of pulmonary function may suggest that respiration is not only associated with motor function, which is mediated mainly by a dopaminergic system, but also with other networks [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%